Immunotherapy and urothelial carcinoma: An overview and future prospectives. (November 2019) - Pierantoni, Francesco; Maruzzo, Marco; Gardi, Mario; Bezzon, Elisabetta; Gardiman, Marina Paola; Porreca, Angelo; Basso, Umberto; Zagonel, Vittorina
Abstract: Background: Urothelial carcinoma (UC) is a common malignancy with a high mortality rate when metastatic. Traditionally, systemic therapy consisted in platinum-based regimens as first-line, with Taxanes or Vinflunine as further lines. Recently, checkpoint inhibitors (CPIs) immunotherapy has emerged as a new therapeutic option. Methods: We searched in Medline, Pubmed and ClinicalTrial.gov databases for the relevant literature, reviewing the results of published trials and the design of ongoing studies involving CPIs in UC. Result: Strong evidence supports the use of CPIs after failure of Cisplatin-based chemotherapy, although no predictive parameter is available so far. Expression of Programmed-Death-1-Ligand has given conflicting results, and is currently indicated only for the selection of Cisplatin-ineligible patients who should receive CPIs. Conclusion: The therapeutic landscape of UC is rapidly changing due to the availability of CPIs. Neoadjuvant trials with CPIs and trials combining two CPIs are promising and will further expand the use of immunotherapy.